Patient-Reported Experiences of Home-Based Breathing Exercises After Cardiac Surgery: A Prospective Questionnaire-Based Cohort Study - Elisabeth Westerdahl PhD, RPT; Charlotte Urell PhD, RPT; Henrik Johansson PhD, RPT; Barbara Cristina Brocki PhD, RPT; Marcus Jonsson PhD, RPT (Journal of Patient Experience)
This study assessed patient-reported experiences and perceived respiratory outcomes of home-based deep breathing exercises 3 months after cardiac surgery. A postal questionnaire was sent to 120 patients at a Swedish university hospital, with 92 respondents (77%). The majority (89%) performed breathing exercises after discharge, with 77% reporting them as very easy to perform. Most patients continued the exercises for 2 to 4 weeks (41%) or 1 to 2 months (20%), typically practicing 3 times per day. The exercises were well tolerated, with 87% experiencing no discomfort. Motivation was generally high—43% felt very motivated, and 78% found the exercises useful. While chest pain was reported as low and 56% experienced improved breathing, nearly half of the respondents reported difficulties with coughing, and 10% sought medical care for respiratory infections. Overall, home-based deep breathing exercises were perceived as beneficial and well accepted. However, engagement and adherence varied, highlighting the need for tailored support to encourage sustained participation.